Human capital formation for the fourth industrial revolution - Atiku, Sulaiman Olusegun, 1980- (Advances in human and social aspects of technology book series., 2020)
"This book examines designing and implementing effective human capital development strategies in human capital formation based on the challenges of the fourth industrial revolution"--